PERANCANGAN ERP (ENTERPRISE RESOURCE PLANNING) MODUL SALES AND INVENTORY PADA PT UV VORTEX - Faldi Azmi; Badie Uddin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This research aims to design and implement an Enterprise Resource Planning (ERP) system using the Sales and Inventory module from Odoo at UV VORTEX, a digital printing business located in North Jakarta. UV VORTEX faces a number of challenges in recording and documenting sales as well as inventory management which still relies on physical records and Microsoft Excel. Comprehensive data collection methods involve literature study, interviews, and direct observation. The main focus is improving UV VORTEX business processes by integrating Odoo Sales and Inventory Modules. The implementation scope includes configuration without customization in Odoo version 16 community, with technical modifications including integrated recording in the Sales Module and separation of product types in the Inventory Module. The results of this research include recommendations for implementing system prototypes, involvement of more related parties, performance evaluation, training and skills development, post-implementation monitoring and support, evaluation of sustainability and flexibility, as well as potential for further research. With the implementation of Odoo, it is hoped that UV VORTEX can increase operational efficiency, improve service quality, and support growth and development in the digital printing industry. This abstract provides a brief overview of research steps to improve UV VORTEX business processes through the implementation of the Odoo ERP system.